الدراسة ا لعددية لنموذج ا يزينغ - ضيف الله, رجاء (University of eloued جامعة الوادي, 2018)
تهدف هذه المذكرة لدراسة الانتقالات الطورية من الدرجة الثانية، والتي تسمى أيضا الظواهر الحرجة. تقتصر الدراسة على الانتقال الفيرومغناطيسي-البارمغناطيسي، لأن هذا هو المثال الأكثر شيوعًا للانتقالات الطورية من الدرجة الثانية، ويمكن بسهولة سحب خصائصه العامة إلى كل الانتقالات الأخرى. نموذج أيزينغ بالغ الأهمية لأنه النموذج الأساسي للفيرومغناطيسية كما يبدي مغنطة تلقائية في بعدين. هناك ثلاثة فصول في هذه المذكرة، الأول مخصص للمفاهيم العامة للإنتقالات الطورية، والفصل الثاني مخصص للمجموعة القانونية. أخيرًا، خُصص الفصل الأخير والأساسي لدراسة نموذج أيزينغ في بعدين بإستعمال تقريب الحقل المتوسط ومحاكاة مونتي كارلو العددية This memoir aims to study second-order phase transitions, also called critical phenomena. The study is restricted to the ferromagnetic-paramagnetic transition; because this is the most familiar example of a second-order phase transition, and its general characteristics can easily be transposed to all the others. The Ising model is so important because it is the basic model of ferromagnetism and exhibits spontaneous magnetization in two dimensions. There are three chapters in this memoir the first one is devoted to the general concepts of phase transitions and the second chapter is devoted to canonical ensemble. Finally, the last and the basic one is devoted to study of Ising model in two dimensions by using mean field approximation and numerical Monte Carlo simulation
مذكرة ماستر تخصص فيزياء
Keywords: نموذجايزينغ – الإنتقالاتالطورية – الإنتقالالفيرومغناطيسي-بارامغناطيس; Ising model - phase transitions - the ferromagnetic-paramagnetic transition